Predicting the Anti-Pulmonary Fibrosis Potential of Physalis angulata Compounds A Computational Study - Muhammad Farid; Assa Aulia Kirana; Nandita Diah Oktaviana; Sofia Rasyda; Dwi Anggraini; Widya Aryana Ramadhania (Biology, Medicine, & Natural Product Chemistry, 2025)
Pulmonary fibrosis is a progressive lung disease characterized by tissue scarring and respiratory decline. Existing treatments have limited efficacy and significant side effects. Physalis angulata, a traditional medicinal plant, shows promise for antifibrotic therapy due to its bioactive compounds potentially targeting key fibrotic pathways. This study aims to predict the potential of Physalis angulata compounds to PI3K/AKT protein as candidates for antifibrotic therapy. Ten active compounds from P. angulata were docked against the PI3K/AKT protein (PDB ID: 2UZT) using AutoDock Vina. Docking was validated by redocking the native ligand. Binding affinities and molecular interactions were analyzed. ADMET properties were predicted via the pkCSM platform to assess pharmacokinetics and toxicity. Myricetrin exhibited the strongest binding affinity (-9.6 kcal/mol), surpassing the native ligand (-9.1 kcal/mol). Other flavonoids, including eriodictyol (-8.9 kcal/mol), naringin (-8.8 kcal/mol), and apigenin (-8.5 kcal/mol), also showed favorable affinities. Critical amino acids involved were Asp184 and Glu121. The redocking RMSD value of 0.893 Ã confirmed methodological accuracy. ADMET predictions revealed high intestinal absorption for tangeretin and apigenin, with no mutagenic or hepatotoxic risks, indicating good pharmacokinetic profiles. Physalis angulata flavonoids exhibit strong PI3K/AKT binding and favorable pharmacokinetics, supporting their potential as antifibrotic agents.